Antiseptic White Honey Liquid Soap Formulation and its Effectiveness against Nosocomial Infections - Resmi Mustarichie (Journal of Global Pharma Technology, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa Multiresisten (PaMR) are the main bacteria that cause nosocomial infections. Prevention of MRSA and PaMR transmission can be done by maintaining a clean body through the use of antiseptic bath soap that is sensitive to this bacterium. This study aimed to carry out a white honey antiseptic liquid soap formula that could be useful for killing MRSA and PaMR bacteria. This research was based on laboratory research on white honey as an antiseptic derived from natural ingredients. Organoleptic examination, pH, viscosity, consistency, antibacterial effectiveness for 56 days of storage, then from the evaluation results of the formula was best done a hedonic test. Statistical calculations with fixed random block complete design models were applied for a conclusion of evaluation tests. The results of the test activity of the liquid shower soap showed that all three formulations had activity against the MRSA and PaMR bacteria. Growth Inhibitory Concentration Minimum preparation of antiseptic liquid bath soap was 12.5% w/v. Antiseptic liquid soap with a concentration of 12.5% had a phenol coefficient of 0.4167 for MRSA bacteria and 0.9 for PaMR bacteria. The comparative test results showed that the best formula (F2) activity was 0.859: 1 against MRSA and 0.7167: 1 against PaMR compared to liquid bath soap in the market. The test results showed that the best liquid bath soap formula based on stability and the lowest GICM value was white honey antiseptic liquid soap with a concentration of 12.5% w/v.Keywords: Antiseptic bath soap, Nosocomial infections, White Honey, Methicillin-Resistant Staphylococcus aureus (MRSA), Multiresistent Pseudomonas aeruginosa (PaMR).